An assessment of the effectiveness of self-service technology in a university enviroment: The case of University of the Witwatersrand - Ngcwabe, Y; Chiliya, N (My University, 2014)
Self-service is basically a method of serving oneself in business-related organisation without the help of an employee. With the exponential increase of the technology, service companies adopt Self-Service Technologies (SSTs) as their innovative tools to create value. A great amount of research has focused on customers’ perspectives of adopting SSTs using factors of SST adoption, attitudes and intentions toward to use the SST. However, studies on the adoption of SSTs at University institutions particularly in South Africa has not been explored extensively. The notion of self-service is positioned as an important part of the overall system where students are to view, input and modify administrative and financial information on themselves, their work and their courses. Convenience is a major benefit of self-service technology and individuals that are not techno savvy or lack technological resources cannot reap the benefits of SSTs to its fullest potential. The study evaluates the attitudes and perceptions that students have regarding SSTs. This research consisted of a self-administered quantitative research questionnaire, which was initially tested using two pilot studies of 30 and 20 respondents respectively. The questionnaire was distributed at the University of the Witwatersrand (Wits) to a sample group of 380 respondents between the ages of 18 to 30. The data collected was analysed using statistical analysis to examine the relationships between the variables in the research model. Results indicate that some students still value face-to-face service encounters, others lack resources to use SSTs and the effect of self-efficacy limits other students from using SSTs to their fullest potential. Perceived waiting time also has a great influence on the actual use and frequency of SSTs.
Keywords: Self- service technology; University environment